2020
DOI: 10.3390/brainsci10110836
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characterization of Oculomotricity in Children with and without Specific Learning Disorders

Abstract: Children with specific learning disorders have been associated with oculomotor problems, with their analysis even suggested to be a potential diagnostic tool. A prospective non-randomized comparative study evaluating 59 children (6–13 years old) divided into three groups was conducted: a control group (CG) including 15 healthy emmetropic children; a group of 18 healthy children with oculomotor abnormalities (OAG); and a group of 26 children diagnosed with specific learning disorders (LDG). In all groups, besid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…The results of the current study in terms of oculomotricity are consistent with those reported by previous authors [ 4 , 5 , 6 , 7 , 31 , 32 , 33 , 34 , 35 ]. Mahone et al [ 5 ] found deficits in oculomotor response (response inhibition) in 60 children with ADHD compared with 60 controls.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The results of the current study in terms of oculomotricity are consistent with those reported by previous authors [ 4 , 5 , 6 , 7 , 31 , 32 , 33 , 34 , 35 ]. Mahone et al [ 5 ] found deficits in oculomotor response (response inhibition) in 60 children with ADHD compared with 60 controls.…”
Section: Discussionsupporting
confidence: 93%
“…A great variety of scientific studies have confirmed the presence of significant alterations in oculomotricity in children with neurodevelopmental disorders [ 4 , 5 , 6 , 7 , 31 , 32 , 33 , 34 , 35 ]. However, these altered oculomotor patterns are not specific to this type of disorders [ 4 ], as they are also present in healthy children, and they have the potential to affect reading [ 36 ]. Therefore, children with oculomotor alterations and reading problems cannot be diagnosed as having a neurodevelopmental disorder, such as dyslexia, as the diagnosis of this type of conditions is very complex and requires a multidisciplinary approach [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some procedures, such as gross observations of eye movements, have found a relationship with reading disability. 26 , 27 Compared to the DEM test, the gross observation of eye movements is considered to have a different accuracy (see validity paragraph below). The NSUCO (Northeastern State University College of Optometry) 26 oculomotor test is a standardized method and scoring of observational eye movement testing (saccades and pursuit).…”
Section: Application Of Dem Testmentioning
confidence: 99%